Regulatory T Cell-Mediated Control of Autoantibody-Induced Inflammation - Fujio, Keishi; Okamura, Tomohisa; Sumitomo, Shuji; Yamamoto, Kazuhiko (Frontiers in Immunology, 2012)
Autoimmune inflammation including autoantibody-mediated inflammation is responsible for the lethal organ damage that occurs during autoimmune diseases. Autoantibody-mediated inflammation can be separated in two components, autoantibody production and local inflammatory responses. Accumulating evidence has suggested that regulatory T cells (Treg) control both antibody production and the numbers and functions of effector cells such as innate cells and T helper cells. Autoantibodies are produced by both the follicular and extrafollicular pathways. Recently, follicular regulatory T cells (TFR) and Qa-1 restricted CD8+ Treg were identified as populations that are capable of suppressing follicular T helper cell (TFH)-mediated antibody production. In local inflammation, CD4+CD25+ Treg have the capacity to control inflammation by suppressing cytokine production in T helper cells. Although complement proteins contribute to autoantibody-mediated local inflammation by activating innate cells, Treg including CD4+CD25+ Treg are able to suppress innate cells, chiefly via IL-10 production. IL-10-secreting T cells such as Tr1 and Tr1-like cells might also play roles in the control of Th17 and innate cells. Therefore, several kinds of Tregs have the potential to control autoimmune inflammation by suppressing both autoantibody production and the local inflammatory responses induced by autoantibodies.